(-13 - y / 2-6) = 3
-13 - y / -4 = 3
-13 - y = -12
y = -1
2006-09-16 05:25:18
·
answer #1
·
answered by عبد الله (ドラゴン) 5
·
0⤊
0⤋
i'm no longer confident I understand your question because you've were given the solutions there.. each and every of the parts of what you desire are precise in the front of you. the classic variety of an equation of a line is Ax + through = C. The coordinate set is (x,y). For answer #a million, you've were given (a million,a million) m=a million/4, so plug in those numbers to get C, the take them out to get the equation. the in worry-free words portion of undergo in recommendations is m = A interior the classic variety #a million: Ax + through = C a million/4x + y = C a million/4(a million) + a million = C a million/4 + a million = C 5/4 = C So, a million/4 x + y = 5/4 #2 -a million/3x + y = C -a million/3(-6) + (-2) = C 2 - 2 = 0 So, -a million/3x + y = 0 aspect-Slope formula is y-y1 = m(x-x1) merely take your 2 coordinates there and positioned them into the equation. the authentic portion of undergo in recommendations is you should maintain the order instantly. #4 (-a million,-7) (a million,3) (-7-3) = m(-a million-a million) -10 = -2m m = 5 etc...
2016-10-16 00:57:33
·
answer #2
·
answered by manca 4
·
0⤊
0⤋
you have a point and a slope given so then you will look in your book for the "Point-Slope" Equation which looks like:
Y - Y1 = M ( X - X1 )
So we will plug in the numbers of our given we get:
Y - -13 = 3 ( X - 2 )
Y1 M X1
after some algebraic clean-up we get
Y + 13 = 3X - 6 <----------Distribute and turn double negative into a positive
Y = 3X - 19 <---------------Subtract 13 from both sides
Which is the formula for the line passing through the two points.
So from here we have the equation and an X coordinate which means we can simply plug in the 6 for X to get
Y = 3 * 6 - 19
Y = 18 - 19
Y = -1
2006-09-16 07:22:51
·
answer #3
·
answered by Mike B 1
·
0⤊
0⤋
Here is the forumula you need to solve this equation:
M=(y2-y1)/(x2-x1)
So, take that foruma and plug in your numbers
3=(y - -13)/(6 - 2)
3=(y+13)/4 now, multiply each side by 4
12=y+13 now, subtract 13 from each side
-1=y
2006-09-16 05:32:14
·
answer #4
·
answered by renferret 3
·
0⤊
0⤋
(6,y) and (2,-13)
3 = (-13 - y)/(2 - 6)
3 = (-13 - y)/(-4)
-13 - y = -12
-y = 1
y = -1
ANS : y = -1
2006-09-16 12:18:53
·
answer #5
·
answered by Sherman81 6
·
0⤊
0⤋
-1 :)
2006-09-16 05:23:29
·
answer #6
·
answered by Stinkypuppy 3
·
0⤊
0⤋